KARAKTERISTIK INFEKSI ULKUS KAKI DIABETIKUM PADA PASIEN DIABETES MELITUS - Irwana, Irwana; Pratama, Kharisma; Ridlo Ronas, Mahin (Jurnal Riset Keperawatan dan Kesehatan, 2024)
ABSTRACT Background: The incidence rate of diabetic foot ulcers is currently reported to reach 4% and which also carries a risk of amputation of up to 10 to 30 times. Infection is one of the causes of worsening diabetic foot wounds where the infection that occurs determines the condition and the length of the healing process Objective: This study aimed to determine the characteristics of diabetic foot ulcer infection in DM patients. Method: This was a quantitative descriptive study. The sampling technique was purposive sampling with a sample size of 50 participants at the Sahabat Care wound care clinic. Data collection used an observation sheet that consist of demographic data and characteristics of diabetic foot ulcer infection. Results: Most of the UKD sufferers were in the late elderly category 27 (54%), female 30 (60%), last education SMA 22 (44%), and worked as housewives 28 (56%). The sthudy showed that most of the characteristics of the infection included the colour around the ulcer that looked pink 22 (73.3%), erythema 17 (56.7%), did not look pale 18 (60%), necrotic 0% 30 (60%), slough 0% 14 (28%), granulation 5% 8 (16%), pain at a moderate level 22 (44%), and odour smelled at a distance of less than one meter 36 (72%). Conclusion: Most people with diabetes mellitus have ulcers with various infections. It is needed for assessment and proper wound care to prevent further complications such as amputation. Future studies should explore the factors that cause infection in patients with recurrent ulcers.